Progressive pseudorheumatoid dysplasia involving a novel CCN6 mutation: a case report - Li, Yu; Huang, Zhengping; Yan, Yun; Guo, Feng; Wei, Gang; Wang, Yue; Xie, Yu (Frontiers in Immunology, 2024)
This letter reports a case of progressive pseudorheumatoid dysplasia (PPRD) with two kinds of WISP3 gene mutation.A case of PPRD was reported.Its clinical profile and the process of diagnosis were analyzed, and the related literature were reviewed. A 15-years old boy, who developed progressive ankle and hip joint pain and enlargement with spine involvement, was diagnosed as PPRD.The erythrocyte sedimentation rate and C-reactjve protein were m normal range, theumatoid factor and anti-CCP antibody were all negative. HLA-B27 was also negative. Cene study discovered two kinds of mutations in Cellular communication network factor 6 (CCN6) gene: c. 802T>C and c.624dup. Radiographic studies revealed spine platyspondyly and shaped beaked, osteoporosis, bilateral symmetric bony enlargements of the interphalangeal joints.Hip shows bilateral acetabulum and femoral head bone marrow edema which revealed hip arthritis. Gene detection, laboratory examination and typical radiographic features are helpful for the diagnosis of PPRD. This is the first report of c. 802T>C and c.624dup mutations in patients with PPD in our country. We deeply appreciate your consideration of our manuscript, and we look forward to receiving comments from the reviewers. If you have any queries, please don't hesitate to contact me at the address below.